2022
DOI: 10.1038/s41536-022-00208-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory matrix-bound nanovesicles mitigate acute and chronic pristane-induced rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and destruction of synovial joints affecting ~7.5 million people worldwide. Disease pathology is driven by an imbalance in the ratio of pro-inflammatory vs. anti-inflammatory immune cells, especially macrophages. Modulation of macrophage phenotype, specifically an M1 to M2, pro- to anti-inflammatory transition, can be induced by biologic scaffold materials composed of extracellular matrix (ECM). The ECM-based immunomodulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 102 publications
0
13
0
Order By: Relevance
“…Consistent with down-regulation of IFN-γ–related signaling, MBV limited the expression of iNOS in CD11b-expressing myeloid dendritic cells in the lung tissue in the present study. MBV have been shown to have a similar effect on iNOS-expressing, M1-like cells in vitro and in vivo in a model of rheumatoid arthritis ( 19 , 21 , 23 ). While these results have been consistently observed after in vitro and in vivo MBV treatment, the specific mechanisms of action remain unknown, and the identification of such mechanisms should be the subject of future studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with down-regulation of IFN-γ–related signaling, MBV limited the expression of iNOS in CD11b-expressing myeloid dendritic cells in the lung tissue in the present study. MBV have been shown to have a similar effect on iNOS-expressing, M1-like cells in vitro and in vivo in a model of rheumatoid arthritis ( 19 , 21 , 23 ). While these results have been consistently observed after in vitro and in vivo MBV treatment, the specific mechanisms of action remain unknown, and the identification of such mechanisms should be the subject of future studies.…”
Section: Discussionmentioning
confidence: 94%
“…These nanovesicles, identified as matrix-bound nanovesicles (MBVs), are a distinct subclass of extracellular vesicle (EV) that are different from fluid-phase exosomes and are enriched in anti-inflammatory and immunoregulatory-associated microRNA, proteins, and lipids (18)(19)(20). Previous studies of administered MBV show their ability to down-regulate proinflammatory immune responses and improve outcomes in animal models of acute ocular injury, rheumatoid arthritis, and chronic heart transplant rejection (23)(24)(25). In addition, MBVs have been shown to have minimal systemic and immune toxicity in vivo and biodistribution to immune tissues such as the spleen through various routes of administration (26).…”
Section: Introductionmentioning
confidence: 99%
“…39 Moreover, compared to HA, the increasing molecular weight of P-HA and PA-HA characterized by gel permeation chromatography (GPC) also suggested that PEG and Ald were sequentially linked to the HA backbone (Figure 1B), and the percentage of Ald modification could be deduced to be about 3.45% accordingly. To modulate the hydrophobicity and antioxidant capacity of the PAM-HA polymeric carrier, PA-HA was further modified with various ratios of Met, and the successful coupling of Met was confirmed by 1 H NMR (the characteristic peak −CH 3 was labeled in the figure) and elemental analysis (EA; Figure 1A and Table S1). The actual grafting rate of Met onto PA-HA can be extrapolated based on the amount of elemental sulfur by EA (as shown in Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The location of immune cells dispersed in the spleen, and their ability to migrate out of the spleen gives the spleen an important role in the immune system [ 21 ]. Regarding the choice of markers for splenic macrophages, this work refers to the studies of Crum et al and Rubio-Navarro et al [ 22 , 23 ] using CD68 + to label total macrophages in the spleen, CD68 + CD86 + CD163 − to denote M1-type macrophages, and CD68 + CD86 − CD163 + to denote M2-type macrophages.…”
Section: Discussionmentioning
confidence: 99%